2021
DOI: 10.1002/aic.17146
|View full text |Cite
|
Sign up to set email alerts
|

Combination of monovalent and divalent sites on an associating species: Application to water

Abstract: This contribution is in honor of Professor Keith E. Gubbins, an international leader in developing advances in statistical mechanics and molecular simulation for engineering applications. The research presented here extends the SAFT model that Chapman proposed and developed while a graduate student with Professor Gubbins. In this manuscript, a thermodynamic perturbation theory within a multi-density formalism framework is extended to model species with a combination of monovalent and divalent association sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Figure 2 shows LDL fraction values from simulations, 12,51,60,73 two‐state model, 52 spectroscopy data 5,21 and from thermodynamic model predictions 7,46,70,72 . There is scatter from the various sources (see also Figure S1 of Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 shows LDL fraction values from simulations, 12,51,60,73 two‐state model, 52 spectroscopy data 5,21 and from thermodynamic model predictions 7,46,70,72 . There is scatter from the various sources (see also Figure S1 of Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
“…An immediate conclusion is that the origin of these anomalies is not included in the models. There have been attempts to modify the models, either by including co‐operativity 72,81 or by including structural changes in the reference fluid 4 . The latter has been successful at describing some of water's anomalies, like the density maximum, but results are still very preliminary 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A complete equation of state for water would include both hydrogen bond cooperativity and a rigorous accounting of the structural transition toward tetrahedral symmetry. There has been progress in recent years on the inclusion of hydrogen bond cooperativity in SAFT approaches 9–11 . It was demonstrated that inclusion of hydrogen bond cooperativity can lead to accurate prediction of hydrogen bonding structure using input solely from a measured dimerization energy and quantum mechanics calculations.…”
Section: Introductionmentioning
confidence: 99%